Concurrent paclitaxel and radiation therapy for the treatment of cutaneous angiosarcoma. (March 2021) - Roy, Amit; Gabani, Prashant; Davis, Elizabeth J.; Oppelt, Peter; Merfeld, Emily; Keedy, Vicky L.; Zoberi, Imran; Chrisinger, John S.A.; Michalski, Jeff M.; Van Tine, Brian; Spraker, Matthew B.
Highlights: Cutaneous angiosarcoma has poor outcomes with no standardized treatment regimen. Paclitaxel-based chemoRT (CRT) was compared to other therapies at two US institutions. Similar oncologic outcomes and improved survival with paclitaxel CRT. Paclitaxel CRT + surgery provided best oncologic outcomes and survival. Paclitaxel CRT + surgery regimen now being studied in a prospective phase II trial. Abstract: Introduction: We compared clinical outcomes in patients with cutaneous angiosarcoma receiving concurrent paclitaxel-based chemoradiotherapy (CRT) vs. other modalities (Non-CRT). Materials and methods: Patients with non-metastatic cutaneous angiosarcoma diagnosed from 1998 to 2018 at two institutions were identified. In the CRT cohort, paclitaxel 80 mg/m 2 weekly was given for up to 12 weeks and patients received radiotherapy (RT) during the final 6 weeks of chemotherapy. The RT dose was 50–50.4 Gy delivered in 1.8–2 Gy per fraction with an optional post-operative boost of 10–16 Gy. Kaplan-Meier and log-rank statistics were used to compare the outcomes between the two groups. P < 0.05 was considered statistically significant. Results: Fifty-seven patients were included: 22 CRT and 35 Non-CRT. The CRT cohort had more patients > 60 years (100% vs. 60%, p < 0.001) and tumors >5 cm (68.2% vs 54.3%, p = 0.023). The median follow-up was 25.8 (1.5–155.2) months. There was no significant difference in 2-year local control (LC), distant control (DC), or progression-free survival (PFS) between the two groups. The 2-year overall survival (OS) was significantly higher for the CRT cohort (94.1% vs. 71.6%, p = 0.033). Amongst the subset of patients in the CRT cohort who received trimodality therapy, the 2-year LC, DC, PFS, and OS was 68.6%, 100%, 68.6%, and 100%, respectively. Conclusion: The use of concurrent paclitaxel CRT demonstrates promising outcomes. Given these results, we are currently evaluating the safety and efficacy of this regimen in prospective, phase 2 trial (NCT 03921008).